Indian Knowledge System and Contemporary Issues - Pranavkumar N. Bhatt (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The Indian Knowledge System (IKS) encompasses a diverse and profound body of knowledge developed over millennia, covering various disciplines, from philosophy, mathematics, and science to arts, literature, and medicine. In contemporary times, IKS is experiencing a renaissance as it interacts with modern scientific and technological developments. However, the challenges to preserving, promoting, and integrating this vast knowledge repository into global academic and practical discourse are immense. This paper explores the Indian Knowledge System in the context of contemporary issues, with a focus on its philosophical foundations, the role of traditional knowledge in modern society, the challenges of preservation, and the integration of IKS into global knowledge systems.